Genetic dissection and simultaneous improvement of drought and low nitrogen tolerances by designed QTL pyramiding in rice - Feng, Bo; Chen, Kai; Cui, Yanru; Wu, Zhichao; Zheng, Tianqing; Zhu, Yajun; Ali, Jauhar; Wang, Bingbing; Xu, Jianlong; Zhang, Wenzhong; Li, Zhikang (Frontiers Media, 2018)
Drought and low nitrogen are the most common abiotic stresses limiting rice productivity in the rainfed rice areas of Asia and Africa. Development and adoption of green super rice (GSR) varieties with greatly improved drought tolerance (DT) and low nitrogen tolerance (LNT) are the most efficient way to resolve this problem. In this study, using three sets of trait-specific introgression lines (ILs) in a Xian (indica) variety Huanghuazhan (HHZ) background, we identified nine DT-QTL and seven LNT QTL by a segregation distortion approach and a genome-wide association study, respectively. Based on performances of DT and LNT and genotypes at the detected QTL, two ILs M79 and M387 with DT and LNT were selected for cross-making to validate the identified QTL and to develop DT and LNT rice lines by pyramiding two DT-QTL (qDT3.9 and qDT6.3) and two LNT-QTL (qGY1 and qSF8). Using four pairs of kompetitive allele specific PCR (KASP) SNP markers, we selected 66 F2 individuals with different combinations of the target DT- and LNT-QTL favorable alleles and they showed expected improvement in DT and/or LNT, which were further validated by the significant improvement in DT and/or LNT of their F3 progeny testing. Based on evaluation of pyramiding lines in F3 lines under drought, low nitrogen (LN) and normal conditions, four promising pyramiding lines having different QTL favorable alleles were selected, which showed significantly improved tolerances to drought and/or LN than HHZ and their IL parents. Our results demonstrated that trait-specific ILs could effectively connect QTL mapping and QTL pyramiding breeding, and designed QTL pyramiding (DQP) using ILs could be more effective in molecular rice breeding for complex quantitative traits